Nosographic profile of soccer injuries according to the age group - Karoline Pegoraro Silveira; Vítor Hugo Santos Assunção; Nercílio Pereira Guimarães Júnior; Suzi Rosa Miziara-Barbosa; Mara Lisiane Moraes Santos; Gustavo Christofoletti; Rodrigo Luiz Carregaro; Silvio Assis Oliveira Júnior (Universidade Federal de Santa Catarina, 2013)
Soccer is one of the world's most popular team sports and corresponds to one ofthe leading causes of sports injuries (SI). This study aimed to analyze the nosographic profile of the sports injuries common to soccer, according to theage group: childhood, youth and adulthood. We selected 209 soccer players, from amateurs to professional players of a sports club from Campo Grande/MS.Participants were divided into four age groups: G1 (childhood), G2 (juvenile),G3 (teenagers) and G4 (adults). To obtain information about the injuries, we used a morbidity survey. Generally, 74 athletes reported sports injuries, with register of 92 SI. Concerning injury types, muscle injuries totalized 43.47%, followed by joint damage (34.78%) and tendon injury (14.13%), respectively (p<0.05).The affected anatomical sites were predominantly lower limbs (91.3%). Contact was the main etiologic mechanism of injuries, integrating almost half of the cases (47.82%), followed by technique (20.65%) and running (19.56%). Training consisted in the main situation of occurrence of SI (74.3%) in G2 and G4; in other groups, occurrence of SI was similar between training and competition situations (p> 0.05). A higher proportion of registers involved medical-therapeutic approach and asymptomatic return. The evidence shows a higher rate of muscle and joint injuries by contact in the lower limbs in soccer practitioners, regardless of age group. The practice of training seemsto be the main cause of injuries in adolescents and adults.